1994
DOI: 10.1002/mc.2940110207
|View full text |Cite
|
Sign up to set email alerts
|

Far less frequent mutations in ras genes than in the p53 gene in skin tumors of xeroderma pigmentosum patients

Abstract: Mutations in Ha-ras, Ki-ras, and N-ras genes in squamous and basal cell carcinomas in patients with xeroderma pigmentosum (XP) were examined by the polymerase chain reaction followed by single-strand conformation polymorphism analysis and direct base sequencing. No mutation was detected in codons 12, 13, and 61 of the ras genes in XP skin tumors. This was in contrast with previous findings of a high frequency of mutation in the p53 gene in skin tumors in XP patients. A novel mutation in codon 6 of the Ki-ras g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 26 publications
5
40
0
2
Order By: Relevance
“…The mutation rate was 38%. These results agreed with previous published results of the analysis of p53 alterations in bladder cancer from the blackfoot disease endemic area in Taiwan (Shibata et al, 1994), but were much lower than seen in UV-induced skin cancers (Sato et al, 1993;Inga, 1998). However, we could not neglect the possibility that UV may be involved in the cancer development.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The mutation rate was 38%. These results agreed with previous published results of the analysis of p53 alterations in bladder cancer from the blackfoot disease endemic area in Taiwan (Shibata et al, 1994), but were much lower than seen in UV-induced skin cancers (Sato et al, 1993;Inga, 1998). However, we could not neglect the possibility that UV may be involved in the cancer development.…”
Section: Discussionsupporting
confidence: 92%
“…Some genes, for example p53, have been found to be involved in carcinogenesis. In ultraviolet (UV)-induced skin cancer Oram et al (1994) found that p53 tumour suppressor gene mutation rate was 50%; a similar mutation rate was found by other authors (Brash et al, 1991;Sato et al, 1993;Ziegler et al, 1993;Matsumura et al, 1996). Most of the mutation types are CC→TT transitions (Lubbe et al, 1994;Nakazawa et al, 1994;Ziegler et al, 1994;Drouin et al, 1997).…”
supporting
confidence: 53%
“…It is also demonstrated that sun light is associated with skin cancer and melanoma in humans (3,14,23). As shown in Table 2, in consistent with many previous studies, UVB-irradiation cannot cause the formation of DNA lesions, which are a primary factor in the development of skin cancer in mice (4,17). It is likely that, together with frequent UVB-irradiation, epidermal cells may also be unstable and an excellent target for the promotion of tumor development (8,9,24).…”
Section: Discussionsupporting
confidence: 74%
“…sequences, and tandem CC to TT transitions at 5?-CC-3? sequences have also been characterized (33)(34)(35). Similar types of p53 base changes are also found in the skin tumors of sunexposed body areas, but not in skin tumors of nonexposed areas (36).…”
Section: Application Of the Shuttle Vector Plasmids To Uv Mutagenesismentioning
confidence: 80%